Pemanfaatan UAV Jenis Quadcopter Dengan Terbang Otomatis Untuk Perbandingan Titik Koordinat Google Map Dengan Glonass - Muhammad Rizki Radhelan; Ery Syafrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Quadcopter is one type of unmanned aerial vehicles (UAV), it is an unmanned aircraft that has 4 motors and uses several components as controller, namely gyro sensor as balance control, Electronic Speed Controller (ESC) as motor speed control, and GPS compass as position control. Purpose of this paper is to create a quadcopter control system using Glonass and Google maps, to find out and analyze the comparison of coordinate points, by determining the first point on Google Map as a reference point in the form of latitude and longitude, then compared with Glonass by flying quadcopter with variations in points and altitude. After testing, the point results from Google Maps and Glonass are compared on Google Earth by entering latitude and longitude. result is below 1m, variations in trajectories, numerous points, wind, different heights do not affect the results of coordinate points captured by the Glonass. Keywords: Quadcopter, Unmanned Aerial Vehicle (UAV), Global Navigation System (GLONASS), Google Maps